2016
DOI: 10.1055/s-0042-113611
|View full text |Cite
|
Sign up to set email alerts
|

Boldine Inhibits Mouse Mammary Carcinoma In Vivo and Human MCF-7 Breast Cancer Cells In Vitro

Abstract: Boldine is an aporphine alkaloid widely consumed in the folk medicine of some regions. Its anticancer potential has been shown but not yet elucidated. We compared the antitumor effect of orally and parenterally applied boldine in mice bearing solid Ehrlich tumor. We also explored the effects of boldine on breast adenocarcinoma MCF-7 cells . Repeated i. p. injections of 30, 60, or 90 mg boldine/kg, either alone or combined with doxorubicin, slowed tumor growth. The latter two doses also prolonged the post-thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In a dosedependent manner, boldine treatment activated p38, extracellular signal-regulated kinase protein (ERK) and JNK in the mitogen-activated protein kinase pathway. 23 Boldine induced apoptosis in breast cancer cells, as indicated by an increased lactate dehydrogenase, increased membrane permeability, and DNA fragmentation. In addition, boldine induces cell-cycle arrest at G2/M phase.…”
Section: Boldine As An Antiproliferative Agent With Cell-cycle Arrest...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a dosedependent manner, boldine treatment activated p38, extracellular signal-regulated kinase protein (ERK) and JNK in the mitogen-activated protein kinase pathway. 23 Boldine induced apoptosis in breast cancer cells, as indicated by an increased lactate dehydrogenase, increased membrane permeability, and DNA fragmentation. In addition, boldine induces cell-cycle arrest at G2/M phase.…”
Section: Boldine As An Antiproliferative Agent With Cell-cycle Arrest...mentioning
confidence: 99%
“…21 Boldine interacts with the peroxisome proliferator-acitvated receptor (PPAR) response element and could modulate PPAR-responsive genes. 22 An in-vitro study 23 showed that boldine reduced the viability and proliferation of Michigan Cancer Foundation (MCF)-7 cells and was cytotoxic to them. It decreased bromodeoxyuridine incorporation and histone H3 phosphorylation, but did not induce apoptosis in this case.…”
Section: Boldine As An Antiproliferative Agent With Cell-cycle Arrest...mentioning
confidence: 99%
“…While another in vivo study against mouse mammary carcinoma showed that intra peritoneal injections of boldine repeatedly slowed tumor growth. In addition, in vitro study against human MCF-7 breast cancer cells revealed that boldine was cytotoxic to MCF-7 cells and reduced cell viability and proliferation [39].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…[ 10 ] but its use has been expanded to treat rheumatoid arthritis, hypertension, diabetes mellitus and cancer for its numerous pharmacological properties. [ 11 ] Studies have reported that boldine exerts anti‐inflammatory, [ 12 ] antioxidant, [ 13 ] anticancer, [ 14 ] antidiabetic, [ 15 ] antipyretic, antiatherogenic, anticonvulsive, [ 16 ] neuroprotective, [ 17 ] nephroprotective, hepatoprotective and cytoprotective effects. [ 8 ] From the liver perspective, boldine has been shown to protect the liver against oxidative stress, cholestasis and drug‐induced liver injury in experimental studies.…”
Section: Introductionmentioning
confidence: 99%